The Urals Localities in the Poetry of Ekaterina Simonova - E. K. Sozina (Историко-географический журнал)
In the Urals’ modern poetry, Ekaterina Simonova is one of the most powerful and interesting poets with a distinctly own voice. The article deals with Simonova’s poetic geography, limited to the Ural region. Simonova came out of the so called «Nizhny Tagil poetry school», Yevgeny Turenko was her and other Tagil poets’ teacher. Since 2013, she has been living in Ekaterinburg, but Nizhny Tagil retains its central importance in her poetry as a city of childhood and youth, a city of poetic origins, a place of memory, and empirically, a city where her parents live and where she visits regularly, so in poetry it also acts as a city-road. Simonova’s poems are close to docu-poetry and resemble oral narratives that naturally gather into free verse. She writes plot poems about space and place, in which a special story is attached to each locus, taken from life, not necessarily personal, often from the life of her family. As a commentary and addition to Simonova’s poems, the article cites her posts from the social network – akin to diary entries, among them the story of «grandmother Matrena» stands out, who once lived in the village of Visimo-Utkinsky, founded by Akinfiy Demidov. The small history of the family is closely connected in this narrative with the big history of the country, in which, of course, Ekaterina Simonova herself is involved.